Local Governments and civil society lead breakthrough for tobacco control: Lessons from Chandigarh and Chennai - Mina Kashiwabara; Rathinum Arul; Hemant Goswami; Jai P Narain; Francisco Armada (Wolters Kluwer Medknow Publications, 2011)
Smoke-free legislation is gaining popularity; however, it must accompany effective implementation to protect people from secondhand smoke (SHS) which causes 600,000 deaths annually. Increasing numbers of smoke-free cities in the world indicate that municipalities have an important role in promoting smoke-free environments. The objectives were to describe the local initiative to promote smoke-free environments and identify the key factors that contributed to the process. Observations were based on a case study on the municipal smoke-free initiatives in Chandigarh and Chennai, India. India adopted the Cigarette and Other Tobacco Products Act in 2003, the first national tobacco control law including smoke-free provisions. In an effort to enforce the Act at the local level, a civil society organization in Chandigarh initiated activities urging the city to support the implementation of the provisions of the Act which led to the initiation of city-wide law enforcement. After the smoke-free declaration of Chandigarh in 2007, Chennai also initiated a smoke-free intervention led by civil society in 2008, following the strategies used in Chandigarh. These experiences resonate with other cases in Asian cities, such as Jakarta, Davao, and Kanagawa as well as cities in other areas of the world including Mexico City, New York City, Mecca and Medina. The cases of Chandigarh and Chennai demonstrate that civil society can make a great contribution to the enforcement of smoke-free laws in cities, and that cities can learn from their peers to protect people from SHS.